„Rasismul structural și instituțional în Europa: o analiză comparativă în 8 state membre ale Uniunii Europene. Probleme cheie și recomandări de politici (2024)” - Adina - Maria Nikolić (Drepturile Omului)
Racism does not always manifest in the form of overt acts such as racial violence or hate crimes, which are visible, explicit, and easily identifiable. Rather, it is deeply embedded within the very fabric of society, operating through the structures of social, economic, and political institutions. This systemic form of racism results in unequal treatment and perpetuates ongoing disadvantages. The current report examines these widespread systems of inequality, which affect both individuals and particular communities at a structural and institutional level, specifically focusing on structural and institutional racism. Its purpose is to analyze the situation in eight EU member states (Czechia, Germany, Greece, Latvia, the Netherlands, Romania, Spain, and Sweden), to present an overview of the current state of affairs, and to provide a preliminary set of recommendations for both national and European authorities.